Thinking through landscape - Berque, Augustin; Berque, Augustin; Feenberg-Dibon, Anne-Marie, 1943- (New York : Routledge, 2013)
"Our attitude to nature has changed over time. This book explores the historical, literary and philosophical origins of the changes in our attitude to nature that allowed environmental catastrophes to happen. It presents a philosophical reflection on human societies' attitude to the environment, informed by the history of the concept of landscape and the role played by the concept of nature in the human imagination and features a wealth of examples from around the world to help understand the contemporary environmental crisis in the context of both the built and natural environment. Thinking Through Landscape locates the start of this change in human labour and urban elites being cut off from nature. Nature became an imaginary construct masking our real interaction with the natural world. The book argues that this gave rise to a theoretical and literary appreciation of landscape at the expense of an effective practical engagement with nature. It draws on Heideggerian ontology and Veblen's sociology, providing a powerful distinction between two attitudes to landscape: the tacit knowledge of earlier peoples engaged in creating the landscape through their work - "landscaping thought"- and the explicit theoretical and aesthetic attitudes of modern city dwellers who love nature while belonging to a civilization that destroys the landscape - "landscape thinking". This book gives a critical survey of landscape thought and theory for students, researchers and anyone interested in human societies' relation to nature in the fields of landscape studies, environmental philosophy, cultural geography and environmental history"--
First edition of La pensée paysagère published 2008 by Bookstorming.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Landscapes; Nature (Aesthetics); Electronic books